The Relationship of Maternal Knowledge and Attitudes with Basic Immunization in Babies Aged 12 Months in The Clinic - Sri Ilawati (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2022)
Immunization is one of the effective methods of increasing immunity for babies. The average immunization rate in Indonesia is only 72%, which is one indicator of low immunization in Indonesia. This is a shocking tragedy and should not have happened. This type of research is analytical research. This research uses a cross-sectional approach. The population and sample in this study were all mothers who had a 12-month-old baby in the Juliana Dalimunthe Tembung Clinic Area, Deli Serdang District, which amounted to 50 people. The data analysis used is bivariate. The results of the study, based on the age of the majority of respondents aged 20-30 years, as many as 29 people (58%), the majority of respondents having high school/vocational education as many as 26 people (26%), the majority of respondents being housewives as many as 24 people (48 %). Relationship between knowledge and basic immunization in infants aged 0-12 months. It can be concluded that there is a relationship between a mother's knowledge and basic immunization for infants aged 0-12 months. Based on the results of the Chi-Square test of significance (α) = 0.05, a p-value of 0.000 (<0.05) was obtained, then Ho was rejected, and Ha was accepted. It can be concluded that there is a relationship between the mother's attitude and basic immunization for infants aged 0-12 months. It is hoped that all mothers will increase their knowledge and attitudes about immunization, and it is expected that mothers who have babies immunize their babies in a health facility for the protection of their baby.